An analysis of potential market of Proton cars in Jordan / Nazliah Nari - Nari, Nazliah (Faculty of Business and Management, 2006)
The key objective of this research is to gather information to assist Proton in preparing a marketing plan based on the feasibility study done and to penetrate new markets in Jordan. Motorists who bought a new passenger car in the last 5 years tend to be young males who are executives and professionals, other white-collar workers or business owners. Mostly tends to own 1 car or in some cases 2 cars. Most new car purchasers are either a first car purchase or a replacement car purchase. Car prices vary significantly from country to country (most expensive in Syria and cheapest in UAE). Jordan motorists tend to prefer cars that perceived to be well balanced stylish, high quality, comfortable, reliable, value for money, good performance and technically advanced. This is where Proton is improving in those areas with a reasonable price and better looks. Toyota is the most popular Japanese car while Nissan is the second most popular. Korean cars have also managed to garner a large share of the car market due to its reasonable price and image of being economical to operate and maintain. The most popular Korean car is Daewoo, followed closely by Hyundai. Proton's brand awareness in Middle East varies from country to country. On the average 1 in 2 motorists who have bought a new passenger car in the last 5 years have heard about Proton. Proton has the highest brand awareness in Jordan (92%) and the lowest in Saudi Arabia (17%). From this studies, it found that it is feasible for Proton to enter the market in Jordan based on the factors highlighted.